Diversity of macroalgae diversity in the tidal waters - Nurfauzi Ahmad; Diana Hernawati; Diki Muhamad Chaidir (JPBIO (Jurnal Pendidikan Biologi), 2021)
The Tidal waters of Sancang beach are habitats for various marine biota, such as macroalgae. This research aims to find out the diversity of macroalgae species in the tidal waters of Sancang Beach, conducted in February-April 2020. This research uses qualitative methods, sampling techniques using purposive sampling with the help of transect belts. The stations used in the search consist of Station 1 in the Ciporeang area, Station 2 in the Cicukangjambe area, and Station 3 in the Cibako area. Each station has one 100-meter transect belt with a plot size of 1 x 1 meter. Ecological index calculations include diversity index, uniformity index, and dominance index. The results showed that 39 types of macroalgae were found consisting of 10 orders, 18 families, 26 genera with a total macroalgae count of 13324 individuals. The average value of the ecological index obtained includes the diversity index (H') 2.15 with the medium category, the uniformity index (E) 0.26 with the low category, and the dominance index (C) 0.19 with the low category.Keywords: Diversity, macroalgae, sancang beach, tidal waters